DEVELOPMENT AND USABILITY EVALUATION OF A WEB-BASED POS FOR HARDWARE STORES USING SUS - Andre Rahmat Kurniawan; Muhammad Arrozi; Yurdan Vebry Endika; Muhammad Afdhal (Jurnal Riset Informatika, 2026)
Small retail businesses such as hardware stores often manage sales, stock, and reporting manually, which can lead to recording errors, slow reporting, and limited decision support. This study develops a web-based Point of Sale (POS) application for a hardware store environment and evaluates its usability using the System Usability Scale (SUS). The POS system supports product and category management, transaction processing (discount and tax), sales reporting with date-range filtering, best-selling product summaries, and CSV export for spreadsheet-based bookkeeping. The research method follows a design-and-build approach, supported by functional validation using black-box testing and usability measurement using SUS. Usability testing involved five respondents who performed task scenarios including creating transactions, opening sales reports, filtering by date range, and exporting CSV data. The SUS results show respondent scores of 40.0, 82.5, 67.5, 77.5, and 90.0, with an average score of 71.5 (SD = 19.41). The average score indicates the system is acceptable and generally usable, although variability suggests different learning needs across users. The study concludes that a web-based POS with integrated reporting and export features can meet operational needs of small hardware stores and achieves an acceptable usability level. Recommendations include improving onboarding and simplifying certain workflows for new users.